Neuromyelitis optica - Jarius, Sven; Paul, Friedemann; Weinshenker, Brian G.; Levy, Michael; Kim, Ho Jin; Wildemann, Brigitte (Nature reviews. Disease Primers, 2020)
Neuromyelitis optica (NMO; also known as Devic syndrome) is a clinical syndrome characterized by attacks of acute optic neuritis and transverse myelitis. In most patients, NMO is caused by pathogenetic serum IgG autoantibodies to aquaporin 4 (AQP4), the most abundant water-channel protein in the central nervous system. In a subset of patients negative for AQP4-IgG, pathogenetic serum IgG antibodies to myelin oligodendrocyte glycoprotein, an antigen in the outer myelin sheath of central nervous system neurons, are present. Other causes of NMO (such as paraneoplastic disorders and neurosarcoidosis) are rare. NMO was previously associated with a poor prognosis; however, treatment with steroids and plasma exchange for acute attacks and with immunosuppressants (in particular, B cell-depleting agents) for attack prevention has greatly improved the long-term outcomes. Recently, a number of randomized controlled trials have been completed and the first drugs, all therapeutic monoclonal antibodies, have been approved for the treatment of AQP4-IgG-positive NMO and its formes frustes.